470 Financial and Efficacy Analysis of a Centralised Neck of Femur Fracture Service. (12th October 2021) - Ngo, V; Chan, G; Edmondson, M
Abstract: Aim: Osteoporotic fractures are rising in incidence, costing the National Health Service up to £1.1 billion for hospital care. The implementation of the Best Practice Tariff (BPT) of fragility fractures in 2010 created a financial incentive to achieve standards of best practice. In June 2015, a dedicated hip fracture unit (HFU) was set up at Princess Royal Hospital (PRH). The aim of this study is (A) to assess changes in performance to the BPT after the introduction of a dedicated HFU, and (B) whether the performance of a HFU is affected by direct/indirect presentation to the HFU. Method: The performance of Brighton and Sussex University Hospitals (BSUH) to BPT pre and post HFU was assessed by a retrospective review of BPT performance data between 2015 and 2016. 870 patients who were treated for NOFF at BSUH were reviewed to assess whether the performance of the HFU was impacted by patients presenting either directly (PRH) to the HFU or indirectly (presentation to Royal Sussex County Hospital). Appropriate statistical tests were used to analyse the significant differences between these outcome measures. Results: The comparison between pre and post HFU showed there was a significant increase in the time between A&E admission to ward, theatre or orthogeriatric (OG) assessment (P < 0.001) in patients presenting indirectly to HFU compared to direct presentations. Conclusions: Having a HFU is cost neutral, and advantages of HFU include focusing NOFF care which improves in patient care. BPT achievements could be improved by increasing the direct admission of NOFF to the HFU.